2004
DOI: 10.1002/ijc.20046
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide as a radiosensitizer: Evidence for an intrinsic role in addition to its effect on oxygen delivery and consumption

Abstract: Different nitric oxide (NO)-mediated treatments (e.g., isosorbide dinitrate, insulin and electrical stimulation of the host tissue) have been investigated for their effects on tumor oxygenation and radiation sensitivity. We further address the issue of the role played by modulation of the NO-pathway in tumor radiosensitivity. For this purpose, the local concentration of NO was monitored after treatment in FSaII tumors and a comparison between the sensitivity of LLC tumors implanted both on eNOS ؊/؊ and wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…68 Strong support for the involvement of a nitric oxide pathway came from experiments carried out using eNOS À/À mice. 228 The increase in tumor oxygenation, as well the radiosensitizing effect, was abolished when using eNOS knock-out mice compared with wild type mice. Moreover, by a complete analysis of all nitric oxidemediated treatments, it appeared that it was unlikely that oxygen alone was responsible for the radiosensitizing effect in specific conditions.…”
Section: Manipulation Of Tumor Oxygenation By Pharmacological Intervementioning
confidence: 98%
See 2 more Smart Citations
“…68 Strong support for the involvement of a nitric oxide pathway came from experiments carried out using eNOS À/À mice. 228 The increase in tumor oxygenation, as well the radiosensitizing effect, was abolished when using eNOS knock-out mice compared with wild type mice. Moreover, by a complete analysis of all nitric oxidemediated treatments, it appeared that it was unlikely that oxygen alone was responsible for the radiosensitizing effect in specific conditions.…”
Section: Manipulation Of Tumor Oxygenation By Pharmacological Intervementioning
confidence: 98%
“…Moreover, by a complete analysis of all nitric oxidemediated treatments, it appeared that it was unlikely that oxygen alone was responsible for the radiosensitizing effect in specific conditions. 228 Using spin trapping studies that allowed the quantification of the release of nitric oxide in tumors, we showed that nitric oxide possesses an intrinsic radiosensitizing effect, additive to the effect on oxygen delivery and consumption. 228 There are only a few examples so far that have used in vivo EPR oximetry in which the applied treatment leads to a reduction in tumor pO 2 .…”
Section: Manipulation Of Tumor Oxygenation By Pharmacological Intervementioning
confidence: 99%
See 1 more Smart Citation
“…52,53 On the other hand, it has been reported that NO can act as an intrinsic radiosensitizer in vivo. 54 Mechanistic control of the bystander effect could either reduce radiation damage and potential carcinogenesis in normal tissues by reducing bystander signaling or maximize cell sterilization during radiotherapy by amplifying bystander responses in tumors.…”
mentioning
confidence: 99%
“…Furthermore, nitric oxide has been proposed as an intrinsic radiosensitizer in vivo. (27). It has been reported that the adenoviral gene transfer of the iNOS gene enhances the radiation response of human colorectal cancer associated with alterations in tumor vascularity (28).…”
Section: Discussionmentioning
confidence: 99%